Search for bottom squark pair production in proton–proton collisions at $\sqrt{s}=13$ TeV with the ATLAS detector - ATLAS collaboration (2859 authors) (2016)
The result of a search for pair production of the supersymmetric partner of the Standard Model bottom quark ( $\tilde{b}^{1} $ ) is reported. The search uses 3.2 fb$^{-1}$ of pp collisions at $\sqrt{s}=13$ TeV collected by the ATLAS experiment at the Large Hadron Collider in 2015. Bottom squarks are searched for in events containing large missing transverse momentum and exactly two jets identified as originating from b-quarks. No excess above the expected Standard Model background yield is observed. Exclusion limits at 95 % confidence level on the mass of the bottom squark are derived in phenomenological supersymmetric R-parity-conserving models in which the $\tilde{b}^{1} $ is the lightest squark and is assumed to decay exclusively via $\tilde{b}^{1} → b \tilde{χ }^{01}$ , where $\tilde{χ }^{01}$ is the lightest neutralino. The limits significantly extend previous results, bottom squark masses up to 800 (840) GeV are excluded for the $\tilde{χ }^{01}$ mass below 360 (100) GeV whilst differences in mass above 100 GeV between the $\tilde{b}^{1}$ and the $\tilde{χ }^{01}$ are excluded up to a $\tilde{b}^{1} $ mass of 500 GeV.